Health-Related Quality of Life and Associated Factors: Regional Differences Among Oldest-Old in Brazil - Javanna L. G. da S. Freitas Ms; Jaíza M. M. Silva Ms; Júlia Cristina L. Nóbrega Ms; Raisa F. M. Simões Ms; Juliana B. Medeiros PhD; Ricardo O. Alves PhD; Jair L. F. Santos PhD; Yeda Aparecida O. Duarte PhD; Mayana Zatz PhD; David Matheson PhD; Tarciana N. de Menezes PhD; Silvana Santos PhD (SAGE Publishing, 2022)
Purpose The aim of this research was to investigate the extent to which socioeconomic and regional differences in Brazil may influence the quality of life. To this end, we examined factors associated with health-related quality of life in two populations of oldest-old people, aged 80 and over: one from the Northeast of Brazil and the other from the Southeast. Methods 417 participants aged 80 and over were interviewed face-to-face, 179 from Brejo dos Santos, one of the poorest regions in the Northeast; and 238 from São Paulo, one of the largest urban metropolises in Southeast Brazil. Data, which included socioeconomic and demographic factors, health status, and health-related quality of life, were collected using a structured questionnaire. The dependent variable was determined by the completion rate of the 12-item Short Form Survey and analyzed using multiple logistic regression. Results Although the population of São Paulo had four times as many long-lived women than men, had better literacy levels, used more medications, and presented a greater prevalence of symptoms suggestive of depression in comparison to the Northeast's population, no difference was observed in the proportion of good physical components among the two populations, 54.3% in Brejo dos Santos' oldest-old and 50.4% in São Paulo's ( P = .6272). Quality and quantity of sleep were factors that most affected the health-related quality of life among the oldest-old of Northeast. Conclusion Factors associated with health-related quality of life were different among the oldest-old people of the two locations, thereby corroborating the heterogeneous nature of the longevous population.